The relationship between anxiety level and time management among senior high school students in preparing for the university entrance exam - Tumanggor, Roxsana Devi; Astrid Budi Kurnia (Nurse Point: Journal of Nursing, 2025)
Introduction: The UTBK-SNBT is a crucial college entrance exam for students seeking to pursue higher education. However, the number of students who fail the test highlights the vulnerability of those dealing with mental health issues, including anxiety. Studies have shown that effective time management can reduce the impact of anxiety among students. Therefore, time management is crucial in preparing students for the UTBK-SNBT exam. Objective: This research aims to investigate the relationship between anxiety levels and study time management among senior high school students preparing for the UTBK-SNBT. Method: This descriptive correlation study employs a proportional stratified random sampling technique, with a sample size of 162 students. The instruments used include demographic data, the Hamilton Anxiety Rating Scale (HARS), and the Time Management Questionnaire. Data analysis involved frequency distribution and assessing the relationship between the two variables. Results: The findings indicate that the majority of students were female (84%), that 38% exhibited mild anxiety, and that 41% were classified as having sufficient study time management skills. Bivariate statistical analysis revealed no significant relationship between anxiety levels and study time management, with a p-value of 0.926 and a correlation coefficient of -0.007, indicating a very weak relationship. Conclusion: Future researchers are encouraged to further explore the effectiveness of time management and its indicators to obtain more comprehensive findings.